ESR line width and line shape dependence of Overhauser‐enhanced magnetic resonance imaging. (8th August 2016) - Meenakumari, V.; Utsumi, Hideo; Jawahar, A.; Milton Franklin Benial, A.
Abstract : Electron spin resonance and Overhauser‐enhanced magnetic resonance imaging studies were carried out for various concentrations of 14 N‐labeled 3‐carbamoyl‐2, 2, 5, 5‐tetramethyl‐pyrrolidine‐1‐oxyl in pure water. Overhauser‐enhancement factor attains maxima in the range of 2.5–3 mm concentration. The leakage factor showed an asymptotic increase with increasing agent concentration. The coupling parameter showed the interaction between the electron and nuclear spins to be mainly dipolar in origin. The electron spin resonance parameters, such as the line width, line shape and g‐factor, were determined. The line width analysis confirms that the line broadening is proportional to the agent concentration, and also the agent concentration is optimized in the range of 2.5–3 mm . The line shape analysis shows that the observed electron spin resonance line shape is a Voigt line shape, in which the Lorentzian component is dominant. The contribution of Lorentzian component was estimated using thewinsim package. The Lorentzian component of the resonance line attains maxima in the range of 2.5–3 mm concentration. Therefore, this study reveals that the agent concentration, line width and Lorentzian component are the important factors in determining the Overhauser‐enhancement factor. Hence, the agent concentration was optimized as 2.5–3 mm for in vivo/in vitro electron spin resonance imaging and Overhauser‐enhanced magnetic resonance imaging phantom studies. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Electron spin resonance imaging line width and line shape dependence of Overhauser enhancement study was carried out for 14 N‐labeled carbamoyl‐PROXYL. Overhauser enhancement factor attains maxima in the range of 2.5–3 mm agent concentration. Electron spin resonance line width and Lorentzian line shape analysis confirms that the optimum concentration of nitroxyl spin probe is 2.5–3 mm.